Aspects of Mindfulness-Based Intervention to Reduce Anxiety in Adults with Autism: A Delphi Study - Eldatia Utari Putri; Endang Retno Surjaningrum; Afif Kurniawan (Primenjena Psihologija, 2022)
Anxiety is a common psychological disorder often experienced by adults with autism. Studies suggest a method called Mindfulness to help reduce the disorder. However, experts have not reached an agreement on what aspects of Mindfulness are appropriate for adults with autism. Using the Delphi technique, the current study aims to gather expert consensus on which aspects of Mindfulness can be used to reduce anxiety in adults with autism. Opinions were gathered from a panel of seven Mindfulness experts for adults with autism and from adults with autism who had experience using this method. There were 35 Mindfulness-based intervention items agreed upon that matched the characteristics of adults with autism, but of these, only 28 were appropriate. The items are distributed in several sections: preparation, exercises, concepts, homework, and facilitating autistic characteristics. This consensus was reached through three rounds. Mindfulness can be seen as an alternative method for reducing anxiety levels in adults with autism, especially during social interactions. In addition, it is also possible to apply in a therapeutic setting. However, several factors need to be considered in advance when this intervention is to be implemented in Indonesia.